Minimally invasive strabismus surgery versus paralimbal approach: A randomized, parallel design study is minimally invasive strabismus surgery worth the effort? - Sharma, Richa (Medknow Publications & Media Pvt Ltd, 2014)
INTRODUCTION: Minimal access surgery is common in all fields of medicine. We compared a new minimally invasive strabismus surgery (MISS) approach with a standard paralimbal strabismus surgery (SPSS) approach in terms of post-operative course. MATERIALS AND METHODS: This parallel design study was done on 28 eyes of 14 patients, in which one eye was randomized to MISS and the other to SPSS. MISS was performed by giving two conjunctival incisions parallel to the horizontal rectus muscles; performing recession or resection below the conjunctival strip so obtained. We compared post-operative redness, congestion, chemosis, foreign body sensation (FBS), and drop intolerance (DI) on a graded scale of 0 to 3 on post-operative day 1, at 2-3 weeks, and 6 weeks. In addition, all scores were added to obtain a total inflammatory score (TIS). STATISTICAL ANALYSIS: Inflammatory scores were analyzed using Wilcoxon's signed rank test. RESULTS: On the first post-operative day, only FBS (P =0.01) and TIS (P =0.04) showed significant difference favoring MISS. At 2-3 weeks, redness (P =0.04), congestion (P =0.04), FBS (P =0.02), and TIS (P =0.04) were significantly less in MISS eye. At 6 weeks, only redness (P =0.04) and TIS (P =0.05) were significantly less. CONCLUSION: MISS is more comfortable in the immediate post-operative period and provides better cosmesis in the intermediate period.